A Comparative Study of Halal-Compliant and Non-Halal-Compliant Meat Prices and its Influence on Halal Certification in the Lanao Region, Philippines - Sarip, Norhana S. (Universitas Muhammadiyah Yogyakarta, 2024)
The increasing concern regarding permissible food within Islamic communities has contributed to a recent surge in demand for Halal meat. To address this knowledge gap, the objective of this research is to examine the significance of factors influencing Halal certification and its effect on the pricing of Halal-compliant meat. The study employed a non-experimental descriptive research framework to explore the correlation between two primary uncontrolled variables: the price of Halal-compliant meat and Halal certification. Qualitative data were collected based on the demographic characteristics of meat store proprietors in selected municipalities in Lanao Del Sur and Iligan City. Based on the survey findings, it was determined that consumers in the selected research locale of the Lanao region are willing to pay an additional 10 to 50 pesos (PHP) for Halal-compliant meat compared to non-Halal options, depending on the prevailing market price. The respondents also evaluated the factors that influence halal compliance among proprietors of halal-compliant meat shops in Lanao del Sur. The variable representing accessibility to a Halal Certifying Body shows a coefficient of approximately 13.9605, with a statistically significant p-value of 0.028. This finding indicates a significant positive relationship between accessibility to halal certification and the pricing of Halal-compliant products. Economic planning that aligns with Halal principles is essential for advancing the Halal market by enhancing infrastructure and accreditation criteria, supporting small and medium enterprises, and increasing consumer awareness. By implementing these strategies, the Philippines can position itself as a significant player in the global Halal market, contributing to economic growth, job creation, and cultural diversity, particularly in the Lanao region.